2016
DOI: 10.3892/mmr.2016.4909
|View full text |Cite
|
Sign up to set email alerts
|

Polydatin-induced cell apoptosis and cell cycle arrest are potentiated by Janus kinase 2 inhibition in leukemia cells

Abstract: Polydatin (PD), a natural precursor of resveratrol, has a variety of biological activities, including anti‑tumor effects. However, the underlying molecular mechanisms of the anti-cancer activity of PD has not been fully elucidated. The present study demonstrated that PD significantly inhibited the proliferation of the MOLT-4 leukemia cell line in a dose‑ and time-dependent manner by using Cell Counting Kit‑8 assay. PD also dose-dependently increased the apoptotic rate and caused cell cycle arrest in S phase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“… 17 PD also induced cell cycle arrest and apoptosis in leukemia, lung cancer and colorectal cancer cells. 10 , 18 , 19 However, little is known about the effects of PD on RCC cells.…”
Section: Discussionmentioning
confidence: 99%
“… 17 PD also induced cell cycle arrest and apoptosis in leukemia, lung cancer and colorectal cancer cells. 10 , 18 , 19 However, little is known about the effects of PD on RCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…A significant reduction in motility was observed in both cell lines (34.67% for U-2OS, 40.00% for MG-63; P < 0.05) in response to treatment with polydatin (100 μM, U-2OS; or 200 μM, MG-63) compared with the control group ( Figure 1C). Moreover, the apoptotic rate was significantly increased (36.00% for U-2OS, 19.29% for MG-63; P < 0.05) in both cell lines compared with that observed in the control group ( Figure 1D). In the result of Western blot analysis, we found that in both cell lines polydatin significantly increased the expression of p21, caspase 3, and PAPR, whereas it significantly decreased the expression of Ki67, cyclin A, cyclin E, cyclin-dependent kinase 2 (CDK2), matrix metalloproteinase-2 (MMP-2), MMP-9, and poly(ADP-ribose) polymerase 1 (PARP1) (P < 0.05) ( Figure 1E and 1F).…”
Section: Polydatin Inhibited Progression and Induced Apoptosis In Umentioning
confidence: 77%
“…A previous study also proved that polydatin inhibited radiation-induced apoptosis in lung epithelial cells [14], and another study found that PD also inhibited methylglyoxal-induced apoptosis through reducing ROS and improving mitochondrial function in HUVEC cells [15]. However, in many cancer cells, polydatin exhibits apoptosis-promoting effects, including lung cancer cells, cervical cancer cells, and leukemia cells [1619]. The diverse role of polydatin in cancer cells and normal cells provide a novel possibility in application in cancer radiotherapy.…”
Section: Discussionmentioning
confidence: 99%